Diagnostic hystero-laparoscopy in work-up of female infertility - Rai, Amrita; Mishra, Manju G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Infertility is a growing concern of the society. In many cases the exact cause of infertility may not be elucidated, whether it is tubal, ovarian, uterine, or a combination of factors. This paper aims to understand the role of diagnostic hystero-laparoscopy in evaluation of cases of infertility. Methods: This prospective study included 200 infertile women and it was conducted at department of Obstetrics and Gynaecology, MGM Hospital, during the period between January 2016 to December 2016. All the infertile patients either with primary or secondary infertility were included after thorough evaluation. Results: Out of 200 cases, 118(59%) patients had primary infertility and 82(41%) had secondary infertility. While laparoscopy detected abnormalities in 49% of the cases, significant hysteroscopy findings were noted in only 23.5% of cases. The most common laparoscopic abnormalities were endometriosis (32%) and unilateral tubal lockage (24%). On hysteroscopy, periosteal adhesions were the commonest abnormality in both the groups. Conclusions: Diagnostic hystero-laparoscopy is a safe and cost-effective method and should be considered when there are abnormal HSG results, a past history of pelvic infection, pelvic surgery and /or unexplained secondary infertility during management of infertile couple. Evaluation of certain significant and correctable tubo-peritoneal and intrauterine pathologies which are usually missed by other imaging modalities, can be diagnosed as well as managed in some cases by hystero-laparoscopy.